Development and Countermovements. Reflections on the Conflicts Arising from the Commodification of Collective Land in Morocco - Yasmine Berriane (Revue Internationale de Politique de Développement)
This chapter analyses the links between development and conflict in the context of the protest movements that have arisen in response to the increasing commodification of collective land in Morocco. The transfer of this land, a transfer accompanied by a discourse linking the economic development of collective land to human and social development promoted by the state, renders visible—by exacerbating them—the inequalities inherent in the land tenure system introduced in the colonial era. Among the many forms of inequality, those relating to women’s rights have become particularly important on the political scene thanks to action taken by a particular women’s protest movement. This movement has managed to forge status for itself as a legitimate protest movement and is also contributing to the (re)creation of social boundaries based on the rhetoric of autochthony and on the politicisation of social inequalities based on tribal affiliation.